2019
DOI: 10.3390/toxins11090495
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Two Garlic-Derived Compounds, Propyl Propane Thiosulfonate (PTS) and Propyl Propane Thiosulfinate (PTSO), on Growth and Mycotoxin Production by Fusarium Species In Vitro and in Stored Cereals

Abstract: Two garlic-derived compounds, Propyl Propane Thiosulfonate (PTS) and Propyl Propane Thiosulfinate (PTSO), were examined for their efficacy against mycotoxigenic Fusarium species (F. graminearum, F. langsethiae, F. verticillioides). The objectives were to assess the inhibitory effect of these compounds on growth and mycotoxin production in vitro, and in situ in artificially inoculated wheat, oats and maize with one isolate of each respectively, at different water activity (aw) conditions when stored for up to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Fusarium infections are suppressed with fungicides, the use of resistant cultivars, and the intercropping of Allium spp., which is considered an effective method of Fusarium biological control [ 6 , 7 ]. It has been shown that Fusarium growth can be suppressed by antifungal volatiles such as 2-methyl-2-pentenal and organosulfur compounds and non-volatiles such as spirostanol, furostanol, and steroidal saponins produced by Allium roots [ 8 , 9 , 10 , 11 , 12 ], as well as by Flavobacterium spp. accumulated in Allium rhizospheres [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium infections are suppressed with fungicides, the use of resistant cultivars, and the intercropping of Allium spp., which is considered an effective method of Fusarium biological control [ 6 , 7 ]. It has been shown that Fusarium growth can be suppressed by antifungal volatiles such as 2-methyl-2-pentenal and organosulfur compounds and non-volatiles such as spirostanol, furostanol, and steroidal saponins produced by Allium roots [ 8 , 9 , 10 , 11 , 12 ], as well as by Flavobacterium spp. accumulated in Allium rhizospheres [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, garlic organosulfur derivatives and garlic supplements have been shown to negatively affect the growth of tumor cells and the risk of cancer [12][13][14][15][16][17][18][19]. Antimicrobial, antiviral, and fungitoxicity activities against different pathogens have also been demonstrated [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several OSCs, such as propyl-propane-thiosulfinate (PTS) and propyl-propane thiosulfonate (PTSO) have a potential application in maize storage, mainly due to their antifungal and antimycotoxigenic activity. They could be used in concentrations in the order of parts per million to reduce up to 90% the concentrations of mycotoxins produced by Fusarium [ 18 ]. Moreover, due to their antioxidant and antibacterial activities, PTSO and PTS inserted in a synthetic matrix have been also proposed for usage in active food-packaging to better preserve salads [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%